Local cocoa marketing under pressure: Sustainability certification and new forms of competition in Ghana's cocoa industry - Franziska Ollendorf; Goodlet Ansah (Research Network Sustainable Global Supply Chains, 2022)
In the context of persisting sustainability challenges in the Global Cocoa-Chocolate Chain (GCCC), sustainability certification gained momentum as a major industry response. While much research has been undertaking regarding effects of certification schemes on farming practices and farmers' livelihoods, there is little understanding of how these private sector responses transform the local economy. Taking the case of sustainability certification in the cocoa industry of Ghana, this study provides an empirical insight in effects of the rapid proliferation of sustainability certification on the local marketing environment and new forms of competition among local market players. Applying a lens of Global Value Chain theory, the study offers a discussion on upgrading opportunities for local companies and their responses to certification-linked pressures. In the Ghanaian cocoa sector, t sustainability certification became a key tool of competition for farmers among local buying companies. Yet, due to the lack of pre-financing capacities for the costly implementation of certification schemes, and the lack of off-taking arrangements, local Licensed Buying Companies (LBCs) are structurally disadvantaged with the implementation of certification schemes compared to their transnational counterparts and therefore face a strong tendency of losing market shares. The paper contributes to the study of sustainability in the GCCC in two ways: 1) It provides insights on the functioning of the so far understudied local marketing segment and changing dynamics of competition and governance, and 2) it enlarges the sustainability debate by including structural transformations of the industry linked to the implementation of certification.
Keywords: 330; Kakaoanbau; Kakao; Lieferkette; Nachhaltigkeit; Standardisierung; Wettbewerbsvorteil; Ghana